2021
DOI: 10.1016/j.chest.2021.07.1019
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use Disorder: Friend or Foe in Septic Shock and Associated Mortality Among Geriatric Sepsis Patients With Chronic Kidney or Liver Disease?

Abstract: With the increasing medicinal use of cannabis and potential anti-inflammatory role, we aimed to assess the odds and in-hospital mortality of septic shock with vs. without cannabis use among geriatric sepsis patients with chronic kidney or liver diseases (CKD/CLD) using a nationally representative cohort. METHODS:We queried the National Inpatient Sample (2017) to identify geriatric sepsis patients with concomitant CKD/CLD complicated by septic shock. Primary outcomes (septic shock and associated inpatient morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…62 Dosage and frequency used were not provided. 62 Desai et al 63 researched cannabis use in geriatric patients with CKD and its association with septic shock and mortality. It was found that cannabis use, although frequency was not reported, did not affect the risk of developing septic shock but was associated with a significantly lower inpatient mortality rate.…”
Section: Therapeutic Use Of Cannabismentioning
confidence: 99%
See 1 more Smart Citation
“…62 Dosage and frequency used were not provided. 62 Desai et al 63 researched cannabis use in geriatric patients with CKD and its association with septic shock and mortality. It was found that cannabis use, although frequency was not reported, did not affect the risk of developing septic shock but was associated with a significantly lower inpatient mortality rate.…”
Section: Therapeutic Use Of Cannabismentioning
confidence: 99%
“…It was found that cannabis use, although frequency was not reported, did not affect the risk of developing septic shock but was associated with a significantly lower inpatient mortality rate. 63 Surveys conducted by Collister et al 64 on Canadian adults with CKD and kidney failure found that smoking, consuming edibles, and oil treatments alleviated their symptoms, such as pain, sleep, and restless leg syndrome. Once again, the frequency of use of cannabis products was not reported in the study.…”
Section: Therapeutic Use Of Cannabismentioning
confidence: 99%